Bima Arya's Political Communication Strategy In Efforts For Personal Branding On Instagram Social Media - Susilowati, Susilowati; Kussanti, Devy Putri; Suryani, Ita; Armelsa, Dhefine; Atmaja, Jaka (JURNAL TRIAS POLITIKA, 2025)
This study examines Bima Arya's political communication strategy in his efforts for personal branding on Instagram, using a pragmatism paradigm and a qualitative approach. In the rapidly growing digital era, social media has become an important platform for politicians to build and manage their public image. This research uses a qualitative method with a constructivism paradigm, as the aim of the study is to gain a deep understanding of how Bima Arya communicates his self-image through Instagram and how the audience responds to and constructs meaning from this communication. The findings show that content emphasizing direct engagement, transparency, and responsiveness to public issues has proven effective in increasing audience engagement and strengthening a politician's positive image. Bima Arya has successfully maintained his brand image as "Kang Bima," a politician close to the people, through four stages of political communication strategy on Instagram, with consistency in managing his image, visiting various places with different social issues, and demonstrating that he is still loved by the people of Bogor even after no longer serving as the mayor.